Book Review: van Noort S. & Broad G. 2024: Wasps of the World. A Guide to Every Family. - P. BOGUSCH (European Journal of Entomology)
van Noort S. & Broad G. 2024: Wasps of the World. A Guide to Every Family. Princeton University Press, Princeton, NJ, 240 pp. ISBN 9780691238548. Price USD 29.95/GBP 25.00.